Laser Beam Scintillations of Lidar Operating in Weak Oceanic Turbulence - Baykal, Yahya; Gercekcioglu, Hamza (Optica Publishing Group, 2022)
The formulation of light detection and ranging (LIDAR) systems is derived and examined for the scintillation index, evaluated on-axis, of laser beams in horizontal links in the ocean with weak turbulence by utilizing the Rytov method. These scintillation indices, obtained for the Gaussian beam which is collimated, the limits of plane and spherical waves, are depicted versus the source size, target size, and parameter of the normalized reflector size. It is found that the source size, target size, and normalized reflector size parameter, lessening the scintilla-tion index evaluated on-axis, are approximately 0.44 cm, 56 x 10-4 cm, and 2.2, respectively. Additionally, by using these values that minimize the scintillation index, the variation of the scintillations is shown against the propagation distance, radius of reflector, temperature and salinity fluctuation effects, mean squared temperature, and turbulent kinetic energy dissipation rate per unit mass of fluid at various selected source size and radius of reflector values. (c) 2022 Optica Publishing Group
Laser beam scintillations of LIDAR operating in weak oceanic turbulence
Baykal, Yahya/0000-0002-4897-0474